STRATEGI KONSELING LATIHAN ASERTIF UNTUK MEREDUKSI PERILAKU BULLYING - Cucu Arumsari (Journal of Innovative Counseling : Theory, Practice, and Research, 2017)
Bulying that was experienced by someone affected an anxiety and pressure in life. Therefore, asertif training strategy of counselling is required for reducing bullying. Assertive training strategy of counseling is utilized to reduce an anxiety and increases individual interpersonal by removing bullying effect and ward off bullying activities. Asertif training strategy of counseling for reducing bullying consist of rational, identification, differentiating asertif's behaviour and exploringtarget, role playing, simultaneous training, homework and follow-up, and terminations.